Estructura de la comunidad de peces en el sistema Candelaria-Panlau, Campeche, México - Ayala-Pérez, Luis Amado (1998)
The environmental and ecological patterns of tbe fish community in Candelaria-Panlau system (Mexico) are described. Parameters of the water temperature, salinity and transparency, and density, biomass and diversity of the fish cornmunity were analyzed. Between April 1993 and April 1994 five stations were sampled monthly. The fish community had 50 species (7 926 individuals, 144.7 kg of weight). The abundance and diversity values for the fish cornmunity were: 0.09 ind/m2 ; 1.61 g/m2; 18.25 g/ind; H'n = 1.879; J = 0.475 and D = 5.681. The species with ecological dominance were: Cathorops melanopus, Diapterus rhombeus, Anchoa mitchilli, Sphoeroides testudineus, Bairdiella chrysura, B. ronchus, Cynoscion arenarius, and C. nebulosus. The matrixes of the environmental parameters and of fish abundance, were tested with a factor analysis (principal components extraction method); its graphical representation confmns the dominant species and indicates that salinity, station number five and February are tbe components that characterize the system and the fish community.